If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4=-6x-1/2
We move all terms to the left:
4-(-6x-1/2)=0
We get rid of parentheses
6x+4+1/2=0
We multiply all the terms by the denominator
6x*2+1+4*2=0
We add all the numbers together, and all the variables
6x*2+9=0
Wy multiply elements
12x+9=0
We move all terms containing x to the left, all other terms to the right
12x=-9
x=-9/12
x=-3/4
| B=(3+4a)/4 | | 15+11n=169 | | x-7=32.5 | | 2y+(4×4)=64 | | -3x+-12=4+9 | | 4h=7h-16=6 | | -3x+-4=4x+9 | | (7x+3x)+2=42 | | 9-(2p-1)=45 | | X-10-+7x=15+3x | | (28–4i)–(10–30i)=0 | | 6.6÷3=x | | (5x+10)-15=20 | | r/10+27=30 | | -27y+147=12 | | 30-7y=2 | | 18=m(6)+-2 | | 3-x2=35 | | (4-3x+7x=-8,7 | | 2(10x-12)=4 | | 16x+7=135 | | 162=2(3)^x | | 4^3x=455 | | 5n-4+3n=8 | | 2(3x-3)+4=44 | | 7x-52=-6x | | (5x+5)-7=18 | | -6(x-11)=-45 | | -16x-18=130 | | (14x+5)+(3x-17)=90 | | 7x-52=-6 | | 16^-2x=64 |